Role of prebiotics in enhancing the function of next-generation probiotics in gut microbiota. Issue 8 (23rd March 2023) - Fei, Yiqiu; Chen, Zuobing; Han, Shengyi; Zhang, Shuobo; Zhang, Tianfang; Lu, Yanmeng; Berglund, Björn; Xiao, Hang; Li, Lanjuan; Yao, Mingfei
Abstract: With the development of high-throughput DNA sequencing and molecular analysis technologies, next-generation probiotics (NGPs) are increasingly gaining attention as live bacterial therapeutics for treatment of diseases. However, compared to traditional probiotics, NGPs are much more vulnerable to the harsh conditions in the human gastrointestinal tract, and their functional mechanisms in the gut are more complex. Prebiotics have been confirmed to play a critical role in improving the function and viability of traditional probiotics. Defined as substrates that are selectively utilized by host microorganisms conferring a health benefit, prebiotics are also important for NGPs. This review summarizes potential prebiotics for use with NGPs and clarifies their characteristics and functional mechanisms. Then we particularly focus on illustrating the protective effects of various prebiotics by enhancing the antioxidant capacity and their resistance to digestive fluids. We also elucidate the role of prebiotics in regulating anti-bacterial effects, intestinal barrier maintenance, and cross-feeding mechanisms of NPGs. With the expanding range of candidate NGPs and prebiotic substrates, more studies need to be conducted to comprehensively elucidate the interactions between prebiotics and NGPs outside and inside hosts, in order to boost their nutritional and healthcare applications.